Our solar system - Simon, Seymour (New York : Morrow Junior Books, 1992)
Describes the origins, characteristics, and future of the sun, planets, moons, asteroids, meteoroids, and comets.
Includes index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
5.4
2-3
Keywords: Planets -- Juvenile literature; Planets; Planets; Solar system -- Juvenile literature; Solar system; Solar system